2017
DOI: 10.2196/jmir.6601
|View full text |Cite
|
Sign up to set email alerts
|

Effects on Engagement and Health Literacy Outcomes of Web-Based Materials Promoting Physical Activity in People With Diabetes: An International Randomized Trial

Abstract: BackgroundDeveloping accessible Web-based materials to support diabetes self-management in people with lower levels of health literacy is a continuing challenge.ObjectiveThe objective of this international study was to develop a Web-based intervention promoting physical activity among people with type 2 diabetes to determine whether audiovisual presentation and interactivity (quizzes, planners, tailoring) could help to overcome the digital divide by making digital interventions accessible and effective for peo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
78
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(86 citation statements)
references
References 36 publications
4
78
0
4
Order By: Relevance
“…Giving the patient relevant information and facilitating knowledge about the benefits of the different self-care behaviors like physical activity, diet and self-management, can raise awareness of the disease, which is enhanced by using different features to reinforce the provided information (eg. tips, quizzes) action plan, self-techniques goal-settings, providing feedback regarding their progress and identifying and reaching a solution for potential barriers of the patient during the intervention [26,32,34].…”
Section: Physical Activity and Dietmentioning
confidence: 99%
See 1 more Smart Citation
“…Giving the patient relevant information and facilitating knowledge about the benefits of the different self-care behaviors like physical activity, diet and self-management, can raise awareness of the disease, which is enhanced by using different features to reinforce the provided information (eg. tips, quizzes) action plan, self-techniques goal-settings, providing feedback regarding their progress and identifying and reaching a solution for potential barriers of the patient during the intervention [26,32,34].…”
Section: Physical Activity and Dietmentioning
confidence: 99%
“…Using an mHealth system with advice regarding behavioral and motivational messages, a tracking health app, a Bluetooth device (eg. glucometer) and a web-platform can improve the management and education in their own home [19,26,33,35,43]. The benefits of digital intervention can reduce the frequency of failed contact with patients, and they also have the potential to enhance work practice patterns and health service delivery for clinicians and patients in diabetes management [4].…”
Section: Uc Vs Mhealth Interventionmentioning
confidence: 99%
“…There is a growing body of evidence that explores the potential for using new technology to improve diabetes self-management, and the results seem to be quite mixed. Muller et al (2017) found that web-based materials significantly improved diabetes patients' attitudes and intentions to engage in physical activity. Participants also reported high levels of website satisfaction and would recommend the website to others.…”
Section: Evidence On Impact From Related Interventionsmentioning
confidence: 95%
“…These skills are usually referred to as health literacy, which is defined as 'knowledge, motivation and competences to access, understand, appraise and apply health information' (Sørensen et al, 2012). Lower levels of health literacy are associated with poor health knowledge, health service use, illness management and health outcomes (Muller et al, 2017). In addition, computer literacy and information literacy are also necessary to enable people's use of online information.…”
Section: Evidence On Impact From Related Interventionsmentioning
confidence: 99%
“…Caregivers with different cognitive abilities and from different professional education levels may have considerable differences in the degree of and the time they need for acceptance [18]. At present, health message acceptance can be improved by changing the presentation form of materials, such as by using appropriate pictures, simple grammar and vocabulary, and concise presentation [19][20][21]. The current study aimed to explore the acceptance effects of four commonly used health communication message formats (i.e., gain-framed, loss-framed, present-oriented, and future-oriented).…”
Section: Introductionmentioning
confidence: 99%